Tunable metal-enhanced fluorescence by pH-responsive polyacryloyl hydrazide capped Ag nanoparticles. Issue 11 (19th January 2017) - Yuan, Shuai; Ge, Fengyan; Chen, Yanmin; Cai, Zaisheng
Abstract : A new strategy for metal enhanced fluorescence (MEF) was firstly realized based on the surface plasmon resonance of polyacryloyl hydrazide capped Ag nanoparticles (PAH–Ag NPs). Abstract : A new strategy for metal enhanced fluorescence (MEF) was firstly realized based on the surface plasmon resonance of polyacryloyl hydrazide capped Ag nanoparticles (PAH–Ag NPs). Owing to the pH-responsive swelling–shrinking behavior of the polyacryloyl hydrazide (PAH) polymer, the interaction distance between the Por 4+ dye molecules and Ag NPs can be controlled under pH stimuli. By this method, we successfully achieved a tunable MEF in the pH range from 4 to 9 and 1.97-fold fluorescence enhancement can be obtained at pH = 4 as compared to the reference. The as-prepared PAH–Ag NPs successfully combined pH sensitivity and the controllable MEF effect into one entity by introducing the PAH polymer on the surface of Ag NPs, which is promising for use as materials for selective biological sensing and imaging.